(3JeQjf GdWdGHs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s
(3ChdgG (B:s
(3aj bhdg(B: (3JfHJ HGdOgf(B. (3GSJXgQ GdReNTQj GdKGfj hGddg eLQhQ dCfg eVGa Edjg(B...s
(3BNQgG (B:s
(3cbhdge(B: (3eMeO NjQI Gddg ef Ndbg(B... (3hYdi JbOjQg aGdNjQI fYJ (B... (3NdGaG ddechOj hgPG BNQ eG CQOfG LeYg aj gPG GdeNJUQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B181s
(3cTa GdXfhf(B: (3L(B1(3, U (B152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs